Bio-Inspired Highest Lift-to-Drag-Ratio Fin Shape and Angle for Maximum Surfboard Stability: Flow Around Fish Fins - Megan S. MacNeill; Brian D. Barkdoll (Biomimetics)
Wave surfing is a multi-billion dollar industry involving both maneuverability and speed, yet little research has been performed regarding the highest lift-to-drag-ratio fin shape for these competing qualities. Numerical modeling and laboratory experiments were performed here to identify a bio-inspired fin shape that maximized lateral stability and minimized drag forces, in order to increase surfing maneuverability. Nine fins based on dorsal fins of real fish were tested. Both the CFD and laboratory experiments confirmed that the fin of the same shape as that of the Short-Finned Pilot Whale at an angle of attack of 10° had the greatest lift-to-drag ratios. Flow patterns around fins at a low angle of attack were smooth with negligible flow separation, while at any angle of attack greater than 25°, flow-separation-induced drag forces became excessive.